Implementasi kebijakan jaminan kesehatan nasional di Kabupaten Halmahera Utara - Richard Djiko; Putra Sian Arimawa; Charles H.S. Tangkau (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
The Study aim to examine how the implementation of national health insurance policy and what are the obstacles in implementing national health insurance policy through health insurance administering board (BPJS) in North Halmahera Regency. In this study researchers used descriptive qualitative methods. The data used in this research are primary and secondary data. Data collection used interview technique, documentation and observation. In this study the researchers used data analysis techniques from Miles and Huberman that is data reduction, data presentation and conclusion. The results showed that the implementation of national health insurance policy has not run optimally so there are still many people have not participated as participants of national health insurance. In implementing the policy there are some things that become obstacles such as the Implementor not yet understand well what is the standard operational procedures in service to society. Another problem arising from this policy is the status-level reference service system. Another obstacle encountered by researchers in the field is the lack of human resources and supporting tools, there are still many people who complain about the amount of contributions that must be paid by the community.